SeDiCI (Intellectual Creation Diffusion Service) - De Giusti, Marisa Raquel (2006)
The Intellectual Creation Diffusion Service (SeDiCI) of the UNLP was created with the main objective of communicating to the society all the knowledge acquired in different academic fields of our university. This is how we can return all the efforts that were destined to our public institution. SeDiCI was initially thought as an exclusive reservoir of Thesis and Dissertations, but immediately and after interviewing several of the participants from the different academic units, we had to enlarge the project to include not only text formats but also other types such as musical documents, charts, animations, etc.